Iron-oxide-based twin nanoplates with strong T2 relaxation shortening for contrast-enhanced magnetic resonance imaging. Issue 38 (26th September 2018) - Wei, Ruixue; Zhou, Tiantian; Sun, Chengjie; Lin, Hongyu; Yang, Lijiao; Ren, Bin W.; Chen, Zhong; Gao, Jinhao
Abstract : Iron oxide twin nanoplates with high T 2 relaxivity for in vivo contrast-enhanced magnetic resonance imaging and tumor imaging were reported. Abstract : Iron oxide nanomaterials have been intensively investigated over the past few decades as magnetic resonance imaging (MRI) contrast agents (CAs) due to their favorable magnetism and excellent biocompatibility. However, commercial iron-oxide-nanoparticle-based CAs suffer from low T 2 relaxivity, which significantly limits their applications in the biomedical field. Herein, we report a new type of iron oxide nanoplate (IOP) with an interesting twinning plane, which is fabricated via seed growth. Compared with the conventional iron oxide (IO) spherical nanoparticles, iron oxide twin nanoplates (IOP-13) have a larger effective radius, higher saturation magnetization, and greater anisotropy, resulting in their superior T 2 relaxivity of 571.21 mM −1 s −1 at 0.5 T, which is about six times higher than that of commercial IO nanoparticles. In vivo MR imaging demonstrated that IOP-13 could be used for liver imaging and liver tumor diagnosis with high sensitivity and accuracy, revealing the great potential of IOP-13 as a next-generation CA. This work provides a novel strategy of structure tuning to devise high-performance T 2 contrast agents, which expands the applications of iron oxide nanoparticles in biology and materials.